Formulation of Magneto-Responsive Hydrogels from Dually Cross-Linked Polysaccharides: Synthesis, Tuning and Evaluation of Rheological Properties - Vítková, Lenka; Musilová, Lenka; Achbergerová, Eva; Kolařík, Roman; Mrlík, Miroslav; Korpasová, Kateřina; Mahelová, Leona; Capáková, Zdenka; Mráček, Aleš (International journal of molecular sciences, 2022)
Smart hydrogels based on natural polymers present an opportunity to fabricate responsive scaffolds that provide an immediate and reversible reaction to a given stimulus. Modulation of mechanical characteristics is especially interesting in myocyte cultivation, and can be achieved by magnetically controlled stiffening. Here, hyaluronan hydrogels with carbonyl iron particles as a magnetic filler are prepared in a low-toxicity process. Desired mechanical behaviour is achieved using a combination of two cross-linking routes-dynamic Schiff base linkages and ionic cross-linking. We found that gelation time is greatly affected by polymer chain conformation. This factor can surpass the influence of the number of reactive sites, shortening gelation from 5 h to 20 min. Ionic cross-linking efficiency increased with the number of carboxyl groups and led to the storage modulus reaching 103 Pa compared to 101 Pa-102 Pa for gels cross-linked with only Schiff bases. Furthermore, the ability of magnetic particles to induce significant stiffening of the hydrogel through the magnetorheological effect is confirmed, as a 103-times higher storage modulus is achieved in an external magnetic field of 842 kA·m-1. Finally, cytotoxicity testing confirms the ability to produce hydrogels that provide over 75% relative cell viability. Therefore, dual cross-linked hyaluronan-based magneto-responsive hydrogels present a potential material for on-demand mechanically tunable scaffolds usable in myocyte cultivation.
Keywords: reologie; Polymers; kyselina hyaluronová; smart hydrogels; polysacharidy; Hydrogels; hyaluronan; tissue engineering; Polysaccharides; Hyaluronic Acid; polymery; magnetorheology; Rheology; Schiff base; hydrodynamic radius; hydrogely